At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Sure, let's solve the equation [tex]\( 5(x - 4) = 7x + 5 \)[/tex] step by step.
1. Distribute the 5 on the left side of the equation:
[tex]\[ 5(x - 4) = 5 \cdot x - 5 \cdot 4 = 5x - 20 \][/tex]
So the equation can be rewritten as:
[tex]\[ 5x - 20 = 7x + 5 \][/tex]
2. Combine like terms by moving all terms involving [tex]\( x \)[/tex] to one side and constant terms to the other side. First, let's move [tex]\( 5x \)[/tex] to the right side by subtracting [tex]\( 5x \)[/tex] from both sides:
[tex]\[ 5x - 5x - 20 = 7x - 5x + 5 \][/tex]
This simplifies to:
[tex]\[ -20 = 2x + 5 \][/tex]
3. Next, move the constant term 5 to the left side by subtracting 5 from both sides:
[tex]\[ -20 - 5 = 2x \][/tex]
Which simplifies to:
[tex]\[ -25 = 2x \][/tex]
4. Solve for [tex]\( x \)[/tex] by dividing both sides by 2:
[tex]\[ \frac{-25}{2} = x \][/tex]
This gives:
[tex]\[ x = -12.5 \][/tex]
So, the solution to the equation [tex]\( 5(x - 4) = 7x + 5 \)[/tex] is:
[tex]\[ x = -12.5 \][/tex]
1. Distribute the 5 on the left side of the equation:
[tex]\[ 5(x - 4) = 5 \cdot x - 5 \cdot 4 = 5x - 20 \][/tex]
So the equation can be rewritten as:
[tex]\[ 5x - 20 = 7x + 5 \][/tex]
2. Combine like terms by moving all terms involving [tex]\( x \)[/tex] to one side and constant terms to the other side. First, let's move [tex]\( 5x \)[/tex] to the right side by subtracting [tex]\( 5x \)[/tex] from both sides:
[tex]\[ 5x - 5x - 20 = 7x - 5x + 5 \][/tex]
This simplifies to:
[tex]\[ -20 = 2x + 5 \][/tex]
3. Next, move the constant term 5 to the left side by subtracting 5 from both sides:
[tex]\[ -20 - 5 = 2x \][/tex]
Which simplifies to:
[tex]\[ -25 = 2x \][/tex]
4. Solve for [tex]\( x \)[/tex] by dividing both sides by 2:
[tex]\[ \frac{-25}{2} = x \][/tex]
This gives:
[tex]\[ x = -12.5 \][/tex]
So, the solution to the equation [tex]\( 5(x - 4) = 7x + 5 \)[/tex] is:
[tex]\[ x = -12.5 \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.